Metabolic engineering of Yarrowia lipolytica for the production and secretion of the saffron ingredient crocetin - Tingan Zhou; Young-Kyoung Park; Jing Fu; Piotr Hapeta; Cinzia Klemm; Rodrigo Ledesma-Amaro (Biotechnology for Biofuels and Bioproducts)
Abstract Background Crocetin is a multifunctional apocarotenoid natural product derived from saffron, holding significant promises for protection against various diseases and other nutritional applications. Historically, crocetin has been extracted from saffron stigmas, but this method is hindered by the limited availability of high-quality raw materials and complex extraction processes. To overcome these challenges, metabolic engineering and synthetic biology can be applied to the sustainable production of crocetin. Results We constructed a Yarrowia lipolytica strain using hybrid promoters and copy number adjustment, which was able to produce 2.66 g/L of β-carotene, the precursor of crocetin. Next, the crocetin biosynthetic pathway was introduced, and we observed both the production and secretion of crocetin. Subsequently, the metabolite profiles under varied temperatures were studied and we found that low temperature was favorable for crocetin biosynthesis in Y. lipolytica. Therefore, a two-step temperature-shift fermentation strategy was adopted to optimize yeast growth and biosynthetic enzyme activity, bringing a 2.3-fold increase in crocetin titer. Lastly, fermentation media was fine-tuned for an optimal crocetin output of 30.17 mg/L, bringing a 51% higher titer compared with the previous highest report in shake flasks. Concomitantly, we also generated Y. lipolytica strains capable of achieving substantial zeaxanthin production, yielding 1575.09 mg/L, doubling the previous highest reported titer. Conclusions Through metabolic engineering and fermentation optimization, we demonstrated the first de novo biosynthesis of crocetin in the industrial yeast Yarrowia lipolytica. In addition, we achieved a higher crocetin titer in flasks than all our known reports. This work not only represents a high production of crocetin, but also entails a significant simultaneous zeaxanthin production, setting the stage for sustainable and cost-effective production of these valuable compounds.